2018
DOI: 10.2147/cmar.s167179
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment NRS-2002 scores combined with hematologic inflammation markers are independent prognostic factors in patients with resectable thoracic esophageal squamous cell carcinoma

Abstract: BackgroundThe purpose of this study was to investigate the prognostic values of Nutritional Risk Screening 2002 (NRS-2002) and hematologic inflammation markers in patients with esophageal squamous cell carcinoma (ESCC) receiving curative esophagectomy.Materials and methodsA total of 277 patients with ESCC treated with standard curative esophagectomy were retrospectively analyzed. These patients were grouped for further analysis according to the systemic inflammation score (SIS), the combination of neutrophil-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In addition, NRS 2002 nutritional risk screening tool can help in the identification of malnourished patients who need to be given different nutritional support. It provides theoretical support for the formulation of personalized treatment plans and has good guiding and predictive effects on the nutritional screening of patients with colorectal cancer (14). However, NRS is rarely used in patients with gynecological tumors.…”
Section: Nutritional Risk Screening 2002mentioning
confidence: 99%
“…In addition, NRS 2002 nutritional risk screening tool can help in the identification of malnourished patients who need to be given different nutritional support. It provides theoretical support for the formulation of personalized treatment plans and has good guiding and predictive effects on the nutritional screening of patients with colorectal cancer (14). However, NRS is rarely used in patients with gynecological tumors.…”
Section: Nutritional Risk Screening 2002mentioning
confidence: 99%
“…Those patients with higher values of NLR had lower survival probability 15 . In another prospective study performed in preoperative esophageal patients, NLR, PLR and NRS were found to be promising as prognostic factors of progression-free survival 16 .…”
Section: Discussionmentioning
confidence: 93%
“…Currently, many evaluation methods to screening the nutritional status exist; one is the NRS 2002, a valid method for identifying hospitalised patients at risk and those who will benefit from nutritional treatment 16 . A cohort study adopted the NRS 2002 as a tool for assessing nutritional risk and found this tool can accurately predict the association between nutritional risk and clinical outcome 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SIS was found to be used as an alternative to the modified Glasgow Prognostic Score (mGPS) to improve the prediction of clinical outcomes in patients who underwent curative surgical resection of stage I to IV colorectal cancers (CRCs) in the study of Suzuki Y [5]. SIS has also been testified to predict the prognosis of other cancers, for instance, lung cancer [10,11], colorectal cancer [12][13][14], esophageal squamous cell carcinoma [15][16][17], and gastric cancer [18][19][20][21]. So far, no clinical study has found the correlation and prognostic value of SIS for UTUC, which needs further exploration.…”
Section: Introductionmentioning
confidence: 99%